2021
DOI: 10.1088/1742-6596/2040/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development on Ferrock Mortar Cubes

Abstract: Concrete, after water across the world, the second most broadly utilized material involving 8-10% of all yields of CO2, is predominantly because of cement. This project ultimately aims to determine the potential use of Ferrock as an exceptional replacement for cement in concrete compared with other alternative alternatives. It is a steel-based restraining compound used to form a carbon-negative structure substance utilizing waste material absorbents. The iron residue (an iron business loss) that would end in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
3
2
0
Order By: Relevance
“…1 and set 2 (20% PFA and 20% GGBS replacement) because the use of 10% PFA incorporated better pozzolanic reaction due to increased silica contents and 10% GGBS incorporated the atpar performance of OPC(Samad et al, 2017;Cunliffe et al, 2021). The findings are in line with the contemporary studies where the researchers have suggested up to optimum 15% use of ferrock with OPC(Vijayan et al, 2019;Karthika et al, 2021;Shivani et al, 2022). However, the cement-like characteristics of GGBS and silica-rich PFA suggest 10%PFA+10%GGBS-ferrock-based SCMs as better performing composites than the control, set 1 and set 2 mixes.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…1 and set 2 (20% PFA and 20% GGBS replacement) because the use of 10% PFA incorporated better pozzolanic reaction due to increased silica contents and 10% GGBS incorporated the atpar performance of OPC(Samad et al, 2017;Cunliffe et al, 2021). The findings are in line with the contemporary studies where the researchers have suggested up to optimum 15% use of ferrock with OPC(Vijayan et al, 2019;Karthika et al, 2021;Shivani et al, 2022). However, the cement-like characteristics of GGBS and silica-rich PFA suggest 10%PFA+10%GGBS-ferrock-based SCMs as better performing composites than the control, set 1 and set 2 mixes.…”
supporting
confidence: 90%
“…The performance of all the mixes of set 4 (10%PFA+10%SF) is found to be better than the mixes of set 1 and set 2 (20% PFA and 20% GGBS replacement) because the use of 10% PFA and 10% SF incorporated better pozzolanic reaction due to increased silica contents but overall set 4 exhibited slightly less strength than set 3. The findings are in line with the contemporary studies where the researchers have suggested up to optimum 15% use of ferrock with OPC(Vijayan et al, 2019;Karthika et al, 2021;Shivani et al, 2022). The 10 and 20% composites in set 4 demonstrated the maximum increase in compressive strength with 64.4 MPa on 56 days of curing.…”
supporting
confidence: 90%
See 3 more Smart Citations